2021
DOI: 10.1037/aap0000235
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of perceptions of risk and protective factors for suicide among Bhutanese refugees.

Abstract: Over 100,000 ethnically Nepalese, "Lhotshampa," people experienced systematic oppression, disenfranchisement, and violence during the latter part of the twentieth century. The Lhotshampa people were forced to flee their homes in southern Bhutan and enter refugee camps in Nepal for over 20 years. As of this writing, most Bhutanese refugees have been resettled in other countries (primarily the United States, Canada, and Australia). As the two remaining Nepalese refugee camps prepare to close, a growing suicide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This increased risk of adult suicide has been associated with perceiving oneself as a burden and a lack of a sense of belonging, which are in turn linked to struggles obtaining employment, poor health, and family conflict [33]. Other risk factors for suicide include unemployment, substance use, family discord, isolation and family separation [34,35]. One study of resettled Bhutanese found that three-quarters believed other people would look down on them if they pursued mental health counseling, and this was more common amongst participants without a secondary education [36].…”
Section: Resettled Bhutanese and Somali Bantu Communities In New Englandmentioning
confidence: 99%
“…This increased risk of adult suicide has been associated with perceiving oneself as a burden and a lack of a sense of belonging, which are in turn linked to struggles obtaining employment, poor health, and family conflict [33]. Other risk factors for suicide include unemployment, substance use, family discord, isolation and family separation [34,35]. One study of resettled Bhutanese found that three-quarters believed other people would look down on them if they pursued mental health counseling, and this was more common amongst participants without a secondary education [36].…”
Section: Resettled Bhutanese and Somali Bantu Communities In New Englandmentioning
confidence: 99%
“…Reflecting the current humanitarian crisis in Myanmar, half of the papers in this collection focus on refugees from that country: the Chin living in Malaysia (Cowling & Anderson, 2021; Gosnell et al, 2021), the Karen and Burman living in Thailand (Haroz et al, 2021), and the Rohingyas living in Bangladesh (Mozumder & Islam, 2021). Other papers in this collection focus on Lhotshampa Bhutanese refugees living in the United States (Meyerhoff et al, 2021) and on Sri Lankan populations both internally displaced due to war and tsunami (Demaske et al, 2021; Wessells & Kostelny, 2021) and living abroad as refugees (in Canada; Pandalangat & Kanagaratnam, 2021).…”
mentioning
confidence: 99%
“…In addition, a subset of articles in this collection draws attention to factors that protect forcibly displaced Asian populations against poor psychosocial outcomes. Meyerhoff et al (2021) also identify factors that protect Lhotshampa Bhutanese refugees in the United States against suicide—these include low levels of substance use, destigmatization of mental health concerns, strong social connections, reduced postmigration stressors, increased access to mental health care, and better awareness of migration-related challenges among those providing services to their community. Demaske et al (2021) examine a particular aspect of resilience, personal growth initiative (PGI)—the tendency to deliberately engage in actions that are valued—in internally displaced war-affected Sri Lankans, and find that after controlling for depression, wartime experiences, and demographic factors, PGI is positively associated with life satisfaction (but interestingly not functional impairment, as has been found in other war-affected populations).…”
mentioning
confidence: 99%
See 1 more Smart Citation